Features on contrast-enhanced computed tomography for predicting recurrent esophageal variceal bleeding in patients with hepatocellular carcinoma - Ping-Chien Li; Chien-Cheng Chen (BMC Gastroenterology)
Abstract Background Esophageal varices (EV) bleeding in patients with hepatocellular carcinoma (HCC) and liver cirrhosis is a life-threatening complication. We investigated whether features on multi-detector computed tomography (MDCT) could predict recurrent EV hemorrhage. Materials and methods In this cross-sectional study, we retrospectively reviewed 72 patients with HCC and liver cirrhosis who received endoscopic therapy for EV bleeding between 2017 and 2022 at a single institution. Patients with both available contrast-enhanced CT scans taken before the bleeding episode within 6 months and upcoming 6-month follow-up medical records were included. We measured the diameter of the bulging submucosal EV on contrast-enhanced CT, presence of portal vein thrombosis (PVT), and patent umbilical vein (PUV). Demographic information, HCC staging, cirrhosis status as well as laboratory data were collected. The occurrence of recurrent EV bleeding requiring endoscopic therapy was investigated as the outcome. Results The size of submucosal EVs larger than 9.5 mm was identified as the independent risk factor for recurrent EV bleeding in the next 6 months (the area under a receiver operating characteristic curve, AUROC: 0.816, P < 0.001) with 81.1% sensitivity and 80.0% specificity. The positive predictive value was 81.1%, indicating that high-risk EVs were 1.8 times more likely to bleed within the next six months. Conclusion CT scans exhibit excellent performance in predicting recurrent bleeding over the following 6 months. Aggressive endoscopic ligation or medical treatment for these patients with large EVs may improve survival and quality of life. Trial registration This study was retrospectively registered by the local Institutional Review Board of our hospital (approval No. 202400668B0).